Tethering soluble meprin α in an enzyme complex to the cell surface affects IBD‐associated genes. Issue 6 (27th March 2019) - Peters, Florian; Scharfenberg, Franka; Colmorgen, Cynthia; Armbrust, Fred; Wichert, Rielana; Arnold, Philipp; Potempa, Barbara; Potempa, Jan; Pietrzik, Claus U.; Häsler, Robert; Rosenstiel, Philip; Becker-Pauly, Christoph
ABSTRACT: Biologic activity of proteases is mainly characterized by the substrate specificity, tissue distribution, and cellular localization. The human metalloproteases meprin α and meprin β share 41% sequence identity and exhibit a similar cleavage specificity with a preference for negatively charged amino acids. However, shedding of meprin α by furin on the secretory pathway makes it a secreted enzyme in comparison with the membrane‐bound meprin β. In this study, we identified human meprin α and meprin β as forming covalently linked membrane‐tethered heterodimers in the early endoplasmic reticulum, thereby preventing furin‐mediated secretion of meprin α. Within this newly formed enzyme complex, meprin α was able to be activated on the cell surface and detected by cleavage of a novel specific fluorogenic peptide substrate. However, the known meprin β substrates amyloid precursor protein and CD99 were not shed by membrane‐tethered meprin α. On the other hand, being linked to meprin α, activation of or substrate cleavage by meprin β on the cell surface was not altered. Interestingly, proteolytic activity of both proteases was increased in the heteromeric complex, indicating an increased proteolytic potential at the plasma membrane. Because meprins are susceptibility genes for inflammatory bowel disease (IBD), and to investigate the physiologic impact of the enzyme complex, we performed transcriptome analyses of intestinal mucosa from meprin‐knockout mice. Comparison of the transcriptional gene analysis data with gene analyses of IBD patients revealed that different gene subsets were dysregulated if meprin α was expressed alone or in the enzyme complex, demonstrating the physiologic and pathophysiological relevance of the meprin heterodimer formation.—Peters, F., Scharfenberg, F., Colmorgen, C., Armbrust, F., Wiehert, R., Arnold, P., Potempa, B., Potempa, J., Pietrzik, C. U., Häsler, R., Rosenstiel, P., Becker‐Pauly, C. Tethering soluble meprin α in an enzyme complex to the cell surface affects IBD‐associated genes. FASEB J. 33, 7490–7504 (2019). www.fasebj.org